Diabetes mellitus and its socio-demographic determinants: a population-based study from a rural block of Haryana, India - Jangra, Anuj; Malik, J. S.; Singh, Srishti; Sharma, Nitika (International Journal of Advances in Medicine, 2019)
Background: Diabetes is growing alarmingly in India which is a home to more than 65.1 million people with this disease and this number would increase to 80 million by the year 2030. The rising prevalence of type 2 diabetes mellitus poses a major threat to clinical management, economic growth and social wellbeing of patients. Studying socio epidemiology of diabetes among adults would help in decreasing the manifestation and severity of this NCD, so this study was conducted with the aim to assess the prevalence of diabetes mellitus and its associated socio-demographic factors. Methods: The present study was conducted in rural block of district Rohtak over a period of one year among 1000 study participants aged 15-64years. Fasting blood sugar was measured to evaluate the prevalence of diabetes mellitus. Results: Overall prevalence of diabetes mellitus was 9.2%. It was highest among 55-64years age group (26%), those engaged in service (11.6%), illiterates and upper middle SES (14.3%). Conclusions: The prevalence of diabetes was high in the study population. A holistic approach targeting both individual and social factors is required to tackle this high prevalence.